2010
DOI: 10.1002/ajpa.21350
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrial revelation of early human migrations to the Tibetan Plateau before and after the last glacial maximum

Abstract: As the highest plateau surrounded by towering mountain ranges, the Tibetan Plateau was once considered to be one of the last populated areas of modern humans. However, this view has been tremendously changed by archeological, linguistic, and genetic findings in the past 60 years. Nevertheless, the timing and routes of entry of modern humans into the Tibetan Plateau is still unclear. To make these problems clear, we carried out high-resolution mitochondrial-DNA (mtDNA) analyses on 562 Tibeto-Burman inhabitants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 95 publications
(159 reference statements)
9
88
0
1
Order By: Relevance
“…In this study, Han Chinese samples were collected from four different provinces, Gansu, Henan, Shandong and Shanxi province, which were classed into Northern Han Chinese. AMOVA results and allele distribution of 11 X-STR loci among the four geographic populations and that of between Tibetan and Northern Han populations were consistent with those of a previous study [19]. Evaluation of forensic efficiency of the new 11plex X-STR genotyping system indicated that it is a powerful forensic analysis tool in at least the two studied populations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, Han Chinese samples were collected from four different provinces, Gansu, Henan, Shandong and Shanxi province, which were classed into Northern Han Chinese. AMOVA results and allele distribution of 11 X-STR loci among the four geographic populations and that of between Tibetan and Northern Han populations were consistent with those of a previous study [19]. Evaluation of forensic efficiency of the new 11plex X-STR genotyping system indicated that it is a powerful forensic analysis tool in at least the two studied populations.…”
Section: Discussionsupporting
confidence: 88%
“…Han Chinese can be classified as Northern Han, Central Han and Southern Han, and Tibetan populations are more close to Northern Han Chinese from the perspective of human evolution [17][18][19]. In this study, Han Chinese samples were collected from four different provinces, Gansu, Henan, Shandong and Shanxi province, which were classed into Northern Han Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…It is different from a former method based on the rejection sampling algorithm (Blum & Rosenberg, 2007), and thus is computationally more efficient. We applied the new AFSbased methods to infer the rate of population growth from the 20 haplotypes of European in the NIEHS Environmental Genome Project (Livingston et al, 2004), and to infer the number of ancient maternal lineages of Tibetan populations in late Paleolithic age from 31 mitochondrial DNA samples in Qin et al (2010). The conclusions drawn from the proposed methods are consistent with former studies.…”
Section: Discussionsupporting
confidence: 73%
“…As one can see, the number of maternal founding lineages of the Tibetan populations was high 25,000 years ago. This conclusion is consistent with other studies which suggest that the settlement of the Tibetan population is ancient and possibly has multiple sources of origin (Shi et al, 2008;Zhao et al, 2009;Qin et al, 2010;Peng et al, 2011;Xu et al, 2011). Provided that the inference of number of ancient lineages for autosomal regions is region-specific, it is of great interest to apply this method to genomic data and to explore the variation of the number of ancient lineages along the genome.…”
Section: Inferring the Number Of Founding Lineagessupporting
confidence: 73%
“…1,13 To achieve this objective, mtDNA variation within a number of 246 Nepalese individuals from Kathmandu and eastern Nepal were collected and studied in this study (Supplementary Table S1, Supplementary Material online), and the recently released mtDNA data from Nepal 5 and the neighboring regions, especially those from Tibet, 1,13 northeast and northwest India 9-12,14-17 were also considered. To further understand the Nepalese mtDNA landscape, a total of 21 representative individuals were selected for completely mtDNA genome sequencing in order to unambiguously determine their phylogenetic status (Figure 2).…”
Section: Introductionmentioning
confidence: 99%